INTEGRASI TEKNOLOGI DALAM MANAJEMEN STRATEGIK UNTUK MENINGKATKAN DAYA SAING LEMBAGA PENDIDIKAN - Elin Nurlena; Huda Oktalia; Khauranina Hisaanah; Rukiyah Rukiyah; Wahyu Zikriyanto; Tubagus Mahar Ma'arif; Ika Pratiwi (Universitas Sultan Ageng Tirtayasa, 2026)
Digital transformation has significantly reshaped the management of educational institutions. Institutions are required not only to adapt to technological developments but also to strategically integrate them to enhance competitiveness. This study aims to analyze the role of technology integration in strategic management within educational institutions. A systematic literature review of 25 scholarly articles published between 2020 and 2025 was conducted. The findings indicate that technology integration improves organizational efficiency, learning quality, and data-driven decision making. This study also proposes a conceptual model as its novelty contribution